1960
DOI: 10.1084/jem.111.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Behavior of Staphylococci Within Human Leukocytes

Abstract: Recent studies by Cohn and Morse have indicated that pathogenic strains of staphylococci are not phagocytosed in systems containing rabbit serum and polymorphonuclear leukocytes in the absence of specific, thermostable opsonin (1). These studies have further suggested that both pathogenic and non-pathogenic strains of staphylococci are equally susceptible to rapid destruction within the cytoplasm of rabbit leukocytes once phagocytosis has been accomplished.Previous studies in our laboratory have demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1960
1960
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
(13 reference statements)
2
11
0
Order By: Relevance
“…These differences were statistically significant with a t value of 3.79 and a p value of 0.0003. This observation was in keeping with the findings previously reported with large populations of the same strains (8).…”
Section: Resultssupporting
confidence: 93%
“…These differences were statistically significant with a t value of 3.79 and a p value of 0.0003. This observation was in keeping with the findings previously reported with large populations of the same strains (8).…”
Section: Resultssupporting
confidence: 93%
“…Jensen (16) has shown that a precipitin which, in his studies, is universally present in human sera is rarely found in rabbit sera. Similarly, Rogers and Mellvn (17) have shown that most adult human sera contain a thermostabile opsonin that is usually absent from normal rabbits but was occasionally found in rabbits maintained in the rabbit colony for several months. The differences between human and rabbit sera demonstrated in both the previously reported and present studies are probably a reflection of the frequency with which exposure to staphylococcal antigens occurs in the two species.…”
Section: Discussionmentioning
confidence: 79%
“…The characteristics of this strain have been previously reported (3,4). Inocula ranging from 4.3 X l0 s to 3.1 X I09 culturable bacteria were injected.…”
Section: Methodsmentioning
confidence: 93%
“…Inocula ranging from 4.3 X l0 s to 3.1 X I09 culturable bacteria were injected. This strain has been shown to survive within granulocytes (4 Production of Reticuloendothdial Blockade.--Reticuloendothelial "blockade" was accomplished by intravenous administration of 8.0 ml. of thorotrast 19 to 24 hours prior to clearance studies using the method described by Martin, Kerby, and Holland (7).…”
Section: Methodsmentioning
confidence: 99%